Sensory evaluation of virgin olive oils from organic agriculture and integrated production - Peres, Maria de Fátima (2010)
In the present work four olive groves were selected: two in organic agriculture and two in integrated production. Olives were handpicked at two ripening stages and processed by a low-scale mill with a working capacity of 0.05 tons h-1. Differences between olive oils were evaluated through a sensory quantitative descriptive analysis (QDA) for positive attributes; moreover, some chemical parameters that could be related with bitterness, like phenol content and the specific absorbance at 225 nm (K225), were determined as well. Some analyses were also conducted with an Alpha MOS electronic nose system, FOX 2000.